Gene Ontology curation of the blood–brain barrier to improve the analysis of Alzheimer's and other neurological diseases. (26th October 2021) - Saverimuttu, Shirin C C; Kramarz, Barbara; Rodríguez-López, Milagros; Garmiri, Penelope; Attrill, Helen; Thurlow, Katherine E; Makris, Marios; de Miranda Pinheiro, Sandra; Orchard, Sandra; Lovering, Ruth C
Abstract: The role of the blood–brain barrier (BBB) in Alzheimer's and other neurodegenerative diseases is still the subject of many studies. However, those studies using high-throughput methods have been compromised by the lack of Gene Ontology (GO) annotations describing the role of proteins in the normal function of the BBB. The GO Consortium provides a gold-standard bioinformatics resource used for analysis and interpretation of large biomedical data sets. However, the GO is also used by other research communities and, therefore, must meet a variety of demands on the breadth and depth of information that is provided. To meet the needs of the Alzheimer's research community we have focused on the GO annotation of the BBB, with over 100 transport or junctional proteins prioritized for annotation. This project has led to a substantial increase in the number of human proteins associated with BBB-relevant GO terms as well as more comprehensive annotation of these proteins in many other processes. Furthermore, data describing the microRNAs that regulate the expression of these priority proteins have also been curated. Thus, this project has increased both the breadth and depth of annotation for these prioritized BBB proteins. Database URLhttps://www.ebi.ac.uk/QuickGO/